Chapter 1 Critically mapping a wicked solution to food insecurity - Bennett, Audrey (Taylor & Francis, 2023)
Critical mapping-a problematizing, reflective approach-is the process of compiling and analyzing existing design outcomes (DOs) that address a wicked problem (e.g., food insecurity) in a way that creates a synthesis between equity, justice, and environmental responsibility. Critical mapping begins with identification and operationalization of the wicked problem leading to an integrative literature review of multidisciplinary scholarly sources to identify peer-reviewed DOs that contribute to addressing the wicked problem sustainably. Next, it progresses to charting the sustainable DOs affinitively with four quadrants-top-down and local, top-down and memetic (i.e., widespread), bottom-up and memetic, bottom-up, and local. The resulting visualization, introduced as a wicked solution, facilitates analysis to identify places to intervene in the system, where one can synthesize the impact of existing sustainable DOs to understand where gaps exist for future design innovation or appropriation that has the potential to cumulatively solve the wicked problem over time.